2009
DOI: 10.3233/npm-2009-0081
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care practices in urban slums: Evidence from central India

Abstract: One-third of India's urban population resides in slums and squatters, in extreme poverty conditions. Newborn care is sub-optimal among India's urban poor, yet scarcely documented. We assessed newborn care practices in 11 urban slums of Indore in Central India. Practices such as clean cord care, thermal care, timely initiation of breastfeeding and exclusive breastfeeding upto neonatal period were enquired from 312 mothers of infants aged 2-4 months. Correlates of these practices were identified using multiple l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…12,13 However, such information is still not available for urban resettlement and slum areas, which would be beneficial for designing "need-felt" intervention programs to bring about positive behavioral changes among mothers for infant health. 14 Therefore, this study was undertaken to assess breastfeeding practices, techniques, and related knowledge among mothers in an urban resettlement colony of India.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 However, such information is still not available for urban resettlement and slum areas, which would be beneficial for designing "need-felt" intervention programs to bring about positive behavioral changes among mothers for infant health. 14 Therefore, this study was undertaken to assess breastfeeding practices, techniques, and related knowledge among mothers in an urban resettlement colony of India.…”
mentioning
confidence: 99%
“…12,13 However, such information is still not available for urban resettlement and slum areas, which would be beneficial for designing “need-felt” intervention programs to bring about positive behavioral changes among mothers for infant health. 14…”
mentioning
confidence: 99%
“…Similar results were reported by Kesterton et al from rural Karnataka. [18] A clean material was used to tie the cord in 301(86.1%) of the deliveries which are higher than the findings of the study done in urban slums of Indore by Agarwal et al [19,20] . Among the women who were delivered by unskilled birth attendants majority used unsterile material to tie the cord compared to those delivered by skilled personnel.…”
Section: Discussionmentioning
confidence: 77%
“…home vs. institution had been documented by Varma et al in Uttar Pradesh where a higher percentage (79%) of women who delivered in an institution fed colostrum as compared to those delivered at home (59%) and this difference was statistically significant (p< 0.01). [21] The prevalence of Exclusive breastfeeding was 14.4% subjects among the study participants which is lower than slums in Indore where Agarwal et al reported the prevalence of exclusive breastfeeding as 44.6% [20] . Early initiation of breastfeeding was more in those newborns who were delivered by skilled personnel compared to those delivered by unskilled care providers.…”
Section: Discussionmentioning
confidence: 93%
“…On this basis, Vogel (2017) explored the impact of aging on LP, economic aggregates and social welfare with the further population statistics of the three oldest countries in Europe (France, Germany and Italy) and the rest of EU zone. It was found that there was a spatial aggregating feature in different areas (Agarwal, Sethi, Srivastava, Jha, & Baqui, 2009;Jianmin, 2015). Relying on data from various regions of Italy from 2000 to 2013, Mussini (2018) analyzed the regional labor productivity (RLP) and concluded that the level of LP was the main cause of unbalanced regional development (Meng, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%